Persepsi suami: analisis dampak work family conflict pada kepuasan perkawinan - Rizqi Fauziah; Shinta Doriza; Maya Oktaviani (LP2M Universitas Sarjanawiyata Tamansiswa, 2023)
This study aims to determine the effect of work-family conflict on marital satisfaction from the husband's perception. This research uses the associative quantitative method. In addition, this research uses questionnaires to collect the data. The sample consisted of 100 respondents with the criteria of working husbands and having working wives, having children and residing in South Jakarta. There are 14 items to measure the work-family conflict and 66 to measure marital satisfaction. Based on the Kolmogorov-Smirnov normality test, the significant value (2-tailed) is 0.094 > 0.05, proving the data comes from a normal population. Hypothesis testing using Pearson Product Moment Correlation and analyzed by correlation coefficient test. The results showed that work-family conflict had a negative effect on marital satisfaction from the husband's perception of -0.442, meaning that the higher the work-family conflict, the lower marital satisfaction and vice versa. Future researchers should further develop the methods and measuring instruments used.